IMPLICATIONS AND LEGAL CONSEQUENCES OF IMPLEMENTING A RISK BASED ONLINE SINGLE SUBMISSION SYSTEM FOR LIMITED LIABILITY COMPANY BUSINESS LICENSING - Kusmiati, Susi; Afriana, Anita; Faisal, Pupung (Jurnal Poros Hukum Padjadjaran, 2023)
Limited Liability Company (PT) as a Business Entity must have permits to carry out its business activities legally. Risk-based Online Single Submission (OSS) is designated as a Business Licensing portal based on the level of risk of a business activity in determining the type of business licensing. The purpose of this research is to find out how much influence the implementation of business licensing through the risk-based OSS system has in the business licensing of Limited Liability Companies and to formulate the legal consequences that arise if the Limited Liability Company does not comply with the standards of its business activities. The research method used is a normative juridical approach with analytical descriptive research specifications. Data analysis was carried out using qualitative normative methods. The results of the study show that the implementation of business licensing through the risk-based OSS system in practice has implications for limited liability company business licensing, namely providing convenience for limited liability companies in managing business licensing, because permits are issued at the beginning then the government as the authority will verify compliance with business activity standards. legal consequences that arise if the Limited Liability Company does not fulfill the standards of its business activities is the imposition of administrative sanctions on the Limited Liability Company.